"Why is everyone always angry with me?!": When thinking 'why' leads to generalization. (June 2015) - Van Lier, Jens; Vervliet, Bram; Boddez, Yannick; Raes, Filip
Abstract: Background and objectives: The degree of (over)generalization (to the self, over situations) is an important characteristic of depression and anxiety disorders. Little is known about cognitive mechanisms underlying this (over)generalization. In this context, the present study examined the effect of an abstract processing style (compared to a more concrete processing style) on generalization of angry faces to the self. An abstract processing style refers to thoughts about the meaning, causes and consequences of events or situations ('Why'-thinking). Methods: To test the impact of an abstract processing experimentally, images of angry faces were paired with the name of the participant and happy faces were paired with another person's name while participants adopted either an abstract ('Why') or a concrete ('How') processing style. A surprise recognition task, where participants were asked to indicate whether they had seen the faces before, served as a test of generalization of angry faces to the self. Results: Results indicated that participants who adopted an abstract processing style showed more generalization of angry faces to the self and a trend towards more generalization of happy faces to the other person, relative to participants who adopted a concrete processing style. Limitations: Our sample was a non-clinical student sample and thus conclusions about the generalizability to clinical samples should be done with caution. Conclusions: These results suggest that abstract thought may underlie the generalization of bad/failure/angry feelings toward the self ('Everyone is always angry with me') and of good feelings towards other people ('Everyone is always nicer to other people') that is often seen in depression and social anxiety disorder. Highlights: We compare the effect of abstract vs. concrete processing on (over)generalization. (over)generalization is assessed by a source memory task using angry human faces. Abstract processing results in increased generalization of angry faces to the self. Abstract thought can underlie generalization of bad/angry feelings toward the self.